2015
DOI: 10.1016/j.resp.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to dry resting apnoeas in elite divers while breathing pure oxygen

Abstract: a b s t r a c tPurpose: We hypothesized that the third dynamic phase ( 3) of the cardiovascular response to apnoea requires attainment of the physiological breaking point, so that the duration of the second steady phase ( 2) of the classical cardiovascular response to apnoea, though appearing in both air and oxygen, is longer in oxygen. Methods: Nineteen divers performed maximal apnoeas in air and oxygen. We measured beat-by-beat arterial pressure, heart rate (f H ), stroke volume (SV), cardiac output (Q ). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…This is of particular importance as previous studies have reported similar changes as those seen in the current study, but changes have been interpreted as being the effect of stress caused by being underwater, the ambient temperature, and the physical activity of the divers [3234]. Despite intense studies conducted in recent years, the authors have not found a publication presenting such results concerning the direct effect of external pressure on the cardiovascular system.…”
Section: Discussionsupporting
confidence: 77%
“…This is of particular importance as previous studies have reported similar changes as those seen in the current study, but changes have been interpreted as being the effect of stress caused by being underwater, the ambient temperature, and the physical activity of the divers [3234]. Despite intense studies conducted in recent years, the authors have not found a publication presenting such results concerning the direct effect of external pressure on the cardiovascular system.…”
Section: Discussionsupporting
confidence: 77%
“…# indicates a significant difference between the breath-hold divers and the control group ( # p < 0.05; ## p < 0.01) D-group (n = 13) C-group (n = 9) O 2 consumption rate during apnoea (ml/min/kg) 2.8 (2.7-3.0) # 3.1 (2.9-3.4) CO 2 release rate during apnoea (ml/min/kg) 0.8 (0.6-1.0) # 1.2 (0.9-1.5) Arterial blood pressure dynamic consisted of three distinct phases during apnoea (Fig. 1e), as it was previously observed by Fagoni et al (2015) and Sivieri et al (2015): a short dynamic phase, characterised by rapid changes in blood pressure, a steady-state phase, and a further subsequent dynamic phase, characterised by a continuous increase in blood pressure. The pronounced rise in the blood pressure was related to the so called "struggle" phase (Guaraldi et al 2009) connected with the onset of diaphragmatic contractions.…”
Section: Cardiorespiratory Variablessupporting
confidence: 76%
“…Because of this, we used the mean heart rate value over the period from 60 to 30 s before breathholding as a base level. According to Sivieri et al (2015) and Fagoni et al (2015), we found short dynamic phase at the beginning of breath-holding, characterised by rapid changes of heart rate. Then, the heart rate returned to the base level during the first quarter of apnoea.…”
Section: Cardiorespiratory Variablesmentioning
confidence: 80%
“…Some progress has been made in our knowledge of cough neuronal circuits (Haji et al, 2013; Pitts et al, 2016) from the introduction of the revolutionary computational model of the cough generating neuronal network (Shannon et al, 1998) and the first complex description of cough brainstem neuronal circuitry in cat (Oku et al, 1994; Gestreau et al, 1997; Shannon et al, 2004; Jakus et al, 2008). Further significant knowledge has been gained during last decade about cough-related neurotransmission and neuromodulation at the central level (Bolser, 2009; Cinelli et al, 2015) including the mechanisms and sites of action of antitussive drugs (Mutolo et al, 2010; Poliacek et al, 2010). However, significant gaps remain in our understanding of the central regulatory mechanisms for coughing.…”
Section: Introductionmentioning
confidence: 99%